2023
DOI: 10.3390/genes14040909
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fetal Bovine Acellular Dermal Matrix Seeded with Wharton’s Jelly Mesenchymal Stem Cells for Healing Full-Thickness Skin Wounds

Abstract: The treatment of full-thickness skin wounds is a problem in the clinical setting, as they do not heal spontaneously. Extensive pain at the donor site and a lack of skin grafts limit autogenic and allogeneic skin graft availability. We evaluated fetal bovine acellular dermal matrix (FADM) in combination with human Wharton’s jelly mesenchymal stem cells (hWJ-MSCs) to heal full-thickness skin wounds. FADM was prepared from a 6-month-old trauma-aborted fetus. WJ-MSCs were derived from a human umbilical cord and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…With advanced therapies like growth factors, extracellular matrices, synthetic skin, and negative pressure wound therapy; chronic wound care would have become its specialty [ [9] , [10] , [11] ]. Platelets and their derivatives have a considerable role in tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…With advanced therapies like growth factors, extracellular matrices, synthetic skin, and negative pressure wound therapy; chronic wound care would have become its specialty [ [9] , [10] , [11] ]. Platelets and their derivatives have a considerable role in tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 11 ] reported the construction of artificial periosteum with methacrylamide gelatin hydrogel and Wharton’s jelly microparticles for bone regeneration, which resulted in BM-MSCs recruitment and promotion of cell proliferation in rats. Mansour et al [ 12 ] utilized the fetal bovine acellular dermal matrix seeded with WJ-MSCs for healing full-thickness skin wounds in rats. Ohers researchers demonstrated the electrospun poly (ε-caprolactone) and collagen scaffolds seeded with WJ-MSCs for skin tissue regeneration [ 13 ], silk and gelatin nanofibrous 3D scaffolds for differentiation of WJ-MSCs into islet-like cells [ 14 ], and many others.…”
Section: Introductionmentioning
confidence: 99%